Seroprevalence of hepatitis B antigenemia among dental students in a private South Indian dental institution - Nagpal, Bhuvan; Hegde, Usha; Kulkarni, Madhuri (International Journal of Research in Medical Sciences, 2017)
Background: Hepatitis B is the most important infectious occupational disease for the dental health care workers (DHCWs). DHCWs frequently come in contact with blood and saliva and hence are at risk for Hepatitis B virus (HBV) exposure. Studies indicate that DHCWs, through occupational exposure, may have a 10 times greater risk of becoming a chronic hepatitis B carrier than the average citizen. The study was conducted to estimate the seroprevalence of HBV infection among dental students enrolled at a private dental institution in Mysuru, Karnataka, India. Methods: A cross sectional seroprevalencestudy was conducted which included dental students who were enrolled in the dental institution. Data were collected by administering a standard questionnaire to every student regarding their personal health information. Their blood samples were collected and tested by Enzyme Linked Immunosorbent assay (ELISA) for Hepatitis B surface antigen. Results: 352 dental students who gave consent were screened out of a total of 453 dental students. Out of 352 students, 163 (46%) were vaccinated and 189 (54%) were non-vaccinated. All the dental students were found to be seronegative for HBV infection. Conclusions: Though a low rate of HBV infection was observed among dental students, a significant number of dental students were non-vaccinated which suggests a need for proactive implementation of HBV vaccination programme.